THE INFLUENCE OF CRITICAL THINKING SKILLS AND INTERNET USAGE ON HIGH SCHOOL STUDENT ACHIEVEMENT IN ECONOMIC SUBJECT - Tauada Silalahi; Lona Florentina; Gartima Sitanggang; La Hanu; Humisar Sihombing (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
The problem in this research is the low learning achievement of high school students in economics subject. The purpose of this study was to determine: (1) The Effect of Critical Thinking Ability on High School Students' Learning Achievement in Economics Subjects, (2) The Effect of Internet Use on High School Students' Learning Achievement in Economics Subjects, (3) The Effect of Critical Thinking Ability and Internet Use on High School Student Achievement in Economics. This research uses quantitative methods with data collection techniques using questionnaires and observations. Then test for normality, linearity, and multicollinearity. The data analysis technique used multiple linear regression and to test the research hypothesis using the t-test and F-test. The results of multiple linear regression analysis obtained the equation Y = 36.544 + 0.306X1 + 0.310X2, the t-test on the Critical Thinking Ability variable (X1) obtained tcount> t table (5.637 > 1.661), and the Internet Usage variable (X2) obtained tcount> ttable ( 5,668 > 1,661). While the F-test resulted in the value of Fcount>Ftable (42.811> 3.09). Furthermore, from the coefficient of determination (R2) obtained R square of 0.479 which means Critical Thinking Ability, and the use of the Internet contributed 47.9% to the Learning Achievement of High School Students in Economics Subjects. Based on the results of the study, it was also found that the variable of internet use (X2) is the variable that most influences the learning achievement of high school students in Economics subject, this is indicated by the t-count and coefficient values that are greater than the critical thinking ability variable (X1).